2021
DOI: 10.5354/0719-0581.2021.60642
|View full text |Cite
|
Sign up to set email alerts
|

¡Memo, te vienen a ver! El proceso de investigación como protocolo de visita en la cultura mapuche

Abstract: En este trabajo se analiza la interacción de los niños mapuche con las investigadoras en el contexto natural de sus hogares. Específicamente, se describe la agenda protocolar de visitas que la familia mapuche utiliza en su relación con personas ajenas, y se da cuenta del rol que asumen los niños como anfitriones de las investigadoras. Participaron en este estudio tres familias de comunidades mapuche de la comuna de Galvarino, Chile, cuyos hijos asistían a una escuela rural de la zona. Se utilizó un diseño etn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Thus, they learn about their culture and values through profound observation [18]. Some of the more important cultural patterns are spontaneous cooperation to achieve common objects as well as the motivation and initiative to participate in community activities [33].…”
Section: Mapuche Family Education: Kimeltuwünmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, they learn about their culture and values through profound observation [18]. Some of the more important cultural patterns are spontaneous cooperation to achieve common objects as well as the motivation and initiative to participate in community activities [33].…”
Section: Mapuche Family Education: Kimeltuwünmentioning
confidence: 99%
“…Thus the object of family education is to bring up children to match the ideal of an educated Mapuche person (che); this requires bringing up both boys and girls on an equal footing, based on four objects of education. While it has been observed that differences exist between the roles performed by boys and girls [18,33] and that the value of respect when applied to Mapuche girls transcends the human and embraces the natural world of non-human living beings [17], no gender-based differences are observed when it comes to value content in their upbringing. The four objects are as follows:…”
Section: Mapuche Family Education: Kimeltuwünmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of cultural resistance, children are considered a sociopolitical project for the Mapuche people, through which the culture endures so, they are called weichafe, which means warriors, because they are learning to defend their Mapuche culture in several ways (Alarcón et al, 2018(Alarcón et al, , 2021. In the school children express their culture despite the norms and prohibitions of the educational system; thus, they develop particular forms of participation and learning in contexts other than those from their own culture (Alonqueo et al, 2020).…”
mentioning
confidence: 99%